Bi < 3 + > and Yb < 3 + > co-doped Cs2ZrCl6 double perovskite microcrystal and preparation method of light conversion film thereof

By synthesizing Bi3+ and Yb3+ co-doped Cs2ZrCl6 double perovskite microcrystals in an ionic liquid solvent environment, the problems of short excitation wavelength and low luminous intensity of existing materials are solved, efficient and stable photoelectric performance is achieved, and the process flow is simplified, and costs and environmental pollution are reduced.

CN119570482AInactive Publication Date: 2025-03-07BEIJING UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411454892.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing Cs2ZrCl6 biperovskite materials have problems with slightly short excitation wavelength and slightly low luminous intensity, which limits their application. The traditional preparation process is cumbersome, high cost and serious environmental pollution.

Method used

Bi3+ and Yb3+ co-doped Cs2ZrCl6 biperovskite microcrystals were synthesized in an ionic liquid solvent environment by co-precipitation method, and the dissolution and precipitation process are used to promote the process of dissolution and precipitation, improve crystallinity and photoluminescence performance, and a simple process flow is adopted to achieve industrial production.

Benefits of technology

It realizes ultra-high crystallinity and high photoluminescence quantum yield of Bi3+ and Yb3+ co-doped Cs2ZrCl6 biperovskite microcrystals, has a wide emission spectrum, is simple in process, is low in cost, is non-toxic and environmentally friendly, and is suitable for innovative optical properties and industrial applications of lead-free biperovskite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570482A_ABST
    Figure CN119570482A_ABST
Patent Text Reader

Abstract

The invention discloses a Bi < 3 + > and Yb < 3 + > co-doped Cs2ZrCl6 double perovskite microcrystal and a preparation method of a light conversion film thereof, and particularly discloses a preparation method of the light conversion film by using an ionic liquid as a solvent, dissolving a cesium salt, a zirconium salt, a bismuth salt and an ytterbium salt in the ionic liquid and carrying out a co-precipitation method to obtain the light conversion film of the Bi < 3 + > and Yb < 3 + > co-doped Cs2ZrCl6 double perovskite microcrystal. The selected ionic liquid promotes interaction with cesium salt, zircon salt, bismuth salt and ytterbium salt due to hydrogen bonds and the like, the solubility of the solutes in the ionic liquid is increased, vacancy defects caused by cation migration of the cesium salt, the zircon salt, the bismuth salt and the ytterbium salt are effectively filled with cation parts of the solutes, the crystallinity of the double perovskite is improved by passivating shallow layer defects, and the performance of the double perovskite is improved. And non-radiative recombination is inhibited, so that efficient and stable photoelectric properties are provided. The light conversion material prepared by the three-layer composite hot pressing method has the advantages of high light conversion efficiency, simple preparation process, low cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photoelectric conversion materials, and in particular to a Bi 3+ , Yb 3+ A method for preparing co-doped Cs2ZrCl6 double perovskite microcrystals and light-converting thin films thereof. Background Art

[0002] Silicon solar cells based on photovoltaic power generation technology have attracted much attention as a renewable energy technology application due to their relatively high efficiency. Silicon in silicon solar cells can only efficiently absorb photon energy that is not much different from the bandgap width, and the solar spectrum is mainly concentrated in the near-ultraviolet and visible regions, but photons in this region can only be absorbed by the cell as part of the energy of the silicon bandgap. In order to broaden the spectral response range of silicon solar cells, the solar spectrum is often modulated by down-conversion, converting photons in the high-energy region into photons in the near-infrared region, thereby improving the photoelectric conversion efficiency of the cell.

[0003] Perovskite material originated in 1839. It is a mineral composed of inorganic calcium titanate (CaTiO3). It is widely used as a down-conversion material for silicon solar cells due to its advantages such as high optical absorption, high defect tolerance, and adjustable emission wavelength. The most basic perovskite structure has the general formula of ABX3, and the most common perovskite with good performance is lead-based perovskite APbX3, but the poor stability and toxicity of lead have restricted its promotion in practical applications.

[0004] Among various newly developed lead-free perovskite materials, Cs2ZrCl6 double perovskite was first reported in the 1960s. It has attracted much attention due to its non-toxicity and flexible synthesis method, making it stand out among many zero-dimensional lead-free double perovskites. However, Cs2ZrCl6 has problems such as slightly short excitation wavelength and slightly low luminescence intensity, which limits its application. In order to solve its defects, Xiong et al. from Guangdong University of Technology synthesized Cs2ZrCl6:Bi 3+ , under 355nm light excitation, the Bi 3+ The efficient blue light emission of Cs2ZrCl6:5%Bi 3+ The emission intensity is the highest. However, in the preparation process, organic solvents, silane, etc. are used to modify the perovskite, which is a cumbersome process.

[0005] Light-conversion film is a technology that is achieved by adding wavelength conversion materials to high-transmittance packaging films. This film can absorb ultraviolet light and convert it into blue light that can generate electricity, thereby protecting solar cells from damage by ultraviolet rays while improving power generation efficiency. However, the current light-conversion film has problems such as poor stability, high production costs, and environmental pollution.3+ , Yb 3+ The thin film preparation process of co-doped Cs2ZrCl6 double perovskite microcrystals is simple, low-cost, non-toxic and environmentally friendly, and has high light conversion efficiency. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned Cs2ZrCl6 perovskite microcrystals and provide a Bi with ultra-high crystallinity, ultra-high photoluminescence quantum yield, wide emission spectrum and low toxicity. 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals.

[0007] The Bi of the present invention 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals are prepared by a co-precipitation method using an ionic liquid as a solvent, dissolving cesium salt, zirconium salt, bismuth salt and ytterbium salt in the ionic liquid.

[0008] Another object of the present invention is to provide Bi 3+ , Yb 3+ The invention discloses a method for preparing co-doped Cs2ZrCl6 double perovskite microcrystals. The preparation method is simple, has a short process flow, and is easy to realize industrial production.

[0009] In order to achieve the above object, the method comprises the following steps:

[0010] S1 heats and melts the ionic liquid;

[0011] S2: mixing, stirring and dissolving the zirconium salt, bismuth salt and ytterbium salt with the ionic liquid to prepare a mixed solution;

[0012] S3: dripping the acid solution of cesium salt into the mixed solution, immediately generating a white precipitate, continuing heating and stirring, then cooling and standing to room temperature, pouring out the upper clear liquid, and the lower solution is a double perovskite microcrystalline solution;

[0013] S4 centrifugally wash the double perovskite microcrystal solution with an organic solvent to obtain wet double perovskite microcrystals;

[0014] S5 is obtained by drying and grinding the wet double perovskite microcrystals.

[0015] According to the present invention, the ionic liquid in step S1 is one of imidazole hexafluorophosphate, imidazole tetrafluoroborate, imidazole chloride, imidazole bromide, imidazole acetate, imidazole trifluoroacetate and imidazole nitrate.

[0016] According to the present invention, the heating temperature in step S1 is 60-100°C.

[0017] According to the present invention, the heating time in step S1 is 10 to 100 minutes.

[0018] According to the present invention, the zirconium salt in step S2 is a mixture of one or more of zirconium chloride, zirconium nitrate, zirconium sulfate, zirconium carbonate and zirconium acetate.

[0019] According to the present invention, the bismuth salt in step S2 is a mixture of one or more of bismuth trichloride, bismuth sulfate, bismuth carbonate and bismuth hydroxide.

[0020] According to the present invention, the ytterbium salt in step S2 is a mixture of one or more of ytterbium trichloride, ytterbium nitrate, ytterbium carbonate, ytterbium sulfate and ytterbium hydroxide.

[0021] According to the present invention, the molar ratio of the zirconium salt, the bismuth salt and the ytterbium salt in step S2 is 10:1:0.005-2.

[0022] According to the present invention, the concentration of the zirconium salt, bismuth salt and ytterbium salt in the ionic liquid in step S2 is 0.01-1 mmol / mL.

[0023] According to the present invention, the dissolving temperature in step S2 is 50-100°C.

[0024] According to the present invention, the cesium salt in step S3 is a mixture of one or more of cesium chloride, cesium sulfate, cesium nitrate, cesium carbonate and cesium hydroxide.

[0025] According to the present invention, the acid in step S3 is one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid.

[0026] According to the present invention, the concentration of the cesium salt in step S3 is 0.05-0.5 mmol / mL.

[0027] According to the present invention, the molar ratio of the cesium salt in step S3 to the zirconium salt in step S2 is 2:0.1-5.

[0028] According to the present invention, the heating temperature in step S3 is 50-100°C.

[0029] According to the present invention, the stirring time in step S3 is 20 to 100 minutes.

[0030] According to the present invention, the organic solvent in step S4 is one of ethanol, methanol, ethyl acetate, carbon dichloride, trichloroethylene, carbon tetrachloride, cyclohexane and n-hexane.

[0031] According to the present invention, the centrifugal washing in step S4 is performed 2 to 6 times.

[0032] According to the present invention, the drying temperature in step S5 is 60-100° C., and the drying time is 1-24 hours.

[0033] Another object of the present invention is to provide a method for preparing a light-converting film, which is simple, has a short process flow, and is easy to realize industrial production.

[0034] To achieve the above object, the method for preparing the light-converting film of the present invention comprises the following steps: firstly preparing Bi 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals;

[0035] S6 will Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals are dissolved in a solvent to prepare a microcrystal solution;

[0036] S7 forming the microcrystalline solution into a microcrystalline film through an ultrasonic spraying machine;

[0037] S8: hot pressing the microcrystalline thin film, magnesium fluoride antireflection film and solar cell in sequence.

[0038] According to the present invention, the solvent in step S6 is a mixture of one or more of methanol, ethanol and toluene.

[0039] According to the present invention, the Bi in step S6 3+ , Yb 3+ The concentration of co-doped Cs2ZrCl6 double perovskite microcrystals is 0.5-10 mmol / ml.

[0040] According to the present invention, the speed of the ultrasonic spraying in step S7 is 100-1000 cm / min.

[0041] According to the present invention, the number of ultrasonic spraying in step S7 is 50 to 300 times.

[0042] According to the present invention, the thickness of the magnesium fluoride antireflection film in step S8 is 10-200 nm.

[0043] According to the present invention, the thickness of the solar cell in step S8 is 10-200 nm.

[0044] According to the present invention, the power of the solar cell in step S8 is 10-200w.

[0045] According to the present invention, the temperature of the hot pressing in step S8 is 100-200°C and the pressure is 0.5-10 kg / cm 2 , the time is 100 to 150 seconds.

[0046] Compared with the prior art, the present invention has the following advantages:

[0047] 1) The present invention synthesizes Bi by coprecipitation in an ionic liquid solvent environment system 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals, the ionic liquid promotes its interaction with cesium salts, zirconium salts, bismuth salts, and ytterbium salts due to hydrogen bonds, etc., increasing the solubility of these solutes in the ionic liquid, and its cationic part is effectively filled into the vacancy defects caused by the migration of cations of cesium salts, zirconium salts, bismuth salts, and ytterbium salts. The crystallinity of the double perovskite is improved by passivating shallow defects, and the occurrence of non-radiative recombination is inhibited, thereby providing efficient and stable photoelectric performance.

[0048] 2) The rare earth Yb selected by the present invention 3+ Compared with the emission spectra of other rare earth ions, it is the simplest, with only 2 F 5 / 2 and 2 F 7 / 2 The two energy levels have an energy difference of 1.27 eV and can emit near-infrared light of about 980 nm, which can meet the emission wavelength requirements of near-infrared materials.

[0049] 3) The present invention selects ionic liquid as solvent, which has many advantages such as being green and environmentally friendly, designable, and able to change the molecular solvent environment of traditional chemical reactions.

[0050] 4) The present invention prepares Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals make the prepared double perovskite microcrystals show excellent luminescence properties in the near-infrared region.

[0051] 5) The present invention uses ionic liquid as a solvent system to prepare double perovskite microcrystals. The prepared double perovskite microcrystals have ultra-high crystallinity and ultra-high photoluminescence quantum yield, which provides an innovative strategy for the optical properties of inorganic lead-free double perovskites and provides a new way to develop green, lead-free, stable and efficient double perovskites in the fields of solid-state lighting, optical anti-counterfeiting and information encryption.

[0052] 6) The light conversion material prepared by the three-layer composite hot pressing method of the present invention has the advantages of high light conversion efficiency, simple preparation process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 Bi prepared in Example 1 of the present invention 3+ , Yb 3+ Fluorescence excitation spectra and fluorescence emission spectra of co-doped Cs2ZrCl6 double perovskite microcrystals.

[0054] Figure 2 Bi prepared in Example 2 of the present invention 3+ , Yb 3+Fluorescence excitation spectra and fluorescence emission spectra of co-doped Cs2ZrCl6 double perovskite microcrystals.

[0055] Figure 3 Bi prepared in Example 3 of the present invention 3+ , Yb 3+ Fluorescence excitation spectra and fluorescence emission spectra of co-doped Cs2ZrCl6 double perovskite microcrystals. DETAILED DESCRIPTION

[0056] A kind of Bi 3+ , Yb 3+ A method for preparing co-doped Cs2ZrCl6 double perovskite microcrystals and light-converting thin films thereof, the method comprising the following steps:

[0057] S1 heats and melts the ionic liquid;

[0058] S2: mixing, stirring and dissolving the zirconium salt, bismuth salt and ytterbium salt with the ionic liquid to prepare a mixed solution;

[0059] S3: dripping the acid solution of cesium salt into the mixed solution, immediately generating a white precipitate, continuing heating and stirring, then cooling and standing to room temperature, pouring out the upper clear liquid, and the lower solution is a double perovskite microcrystalline solution;

[0060] S4 centrifugally wash the double perovskite microcrystal solution with an organic solvent to obtain wet double perovskite microcrystals;

[0061] S5 is obtained by drying and grinding the wet double perovskite microcrystals.

[0062] According to the present invention, the ionic liquid in step S1 is one of imidazole hexafluorophosphate, imidazole tetrafluoroborate, imidazole chloride, imidazole bromide, imidazole acetate, imidazole trifluoroacetate, imidazole nitrate and imidazole imide.

[0063] Preferably, the ionic liquid is an imidazole imide salt.

[0064] More preferably, the imidazole imide salt is one of 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide salt, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-butyl-2,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-octyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt and 1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.

[0065] Selected imidazolidinium salt N atom and Zr 4+ , Cs + 、Bi 3+ etc. have interaction forces, and Zr 4+ , Cs + 、Bi3+ It has a passivation effect, which improves the crystallinity of double perovskite by passivating shallow defects and inhibits the occurrence of non-radiative recombination, thereby providing efficient and stable optoelectronic performance.

[0066] According to the present invention, the molar ratio of the zirconium salt, the bismuth salt and the ytterbium salt in step S2 is 10:1:0.005-2.

[0067] Preferably, the molar ratio of the zirconium salt, the bismuth salt and the ytterbium salt is 10:1:0.05-1.

[0068] Within this ratio range, double perovskite can achieve efficient blue light emission and has the widest emission bandwidth, achieving the best optical performance.

[0069] According to the present invention, the concentration of the zirconium salt, bismuth salt and ytterbium salt in the ionic liquid in step S2 is 0.01-1 mmol / mL.

[0070] Preferably, the concentration of the zirconium salt, bismuth salt and ytterbium salt in the ionic liquid is 0.1-1 mmol / mL.

[0071] According to the present invention, the molar ratio of the cesium salt in step S3 to the zirconium salt in step S2 is 2:0.1-5.

[0072] Preferably, the molar ratio of the cesium salt in step S3 to the zirconium salt in step S2 is 2:1 to 1.5. If the ratio of zirconium salt is too low, the crystal structure and stability will be reduced, and a low ratio of cesium salt will also reduce the photoelectric conversion efficiency, and an appropriate ratio of cesium salt to zirconium salt can also improve the environmental stability of perovskite.

[0073] A method for preparing a light-converting film comprises the following steps: firstly preparing Bi 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals;

[0074] S6 will Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals are dissolved in a solvent to prepare a microcrystal solution;

[0075] S7 forming the microcrystalline solution into a microcrystalline film through an ultrasonic spraying machine;

[0076] S8: hot pressing the microcrystalline thin film, magnesium fluoride antireflection film and solar cell in sequence.

[0077] According to the present invention, the Bi in step S6 3+ , Yb 3+ The concentration of co-doped Cs2ZrCl6 double perovskite microcrystals is 1 to 10 mmol / ml.

[0078] Preferably, the concentration of the double perovskite microcrystals is 1 to 5 mmol / ml.

[0079] According to the present invention, the speed of the ultrasonic spraying in step S7 is 100-1000 cm / min.

[0080] Preferably, the speed of the ultrasonic spraying is 200-600 cm / min.

[0081] According to the present invention, the number of ultrasonic spraying in step S7 is 50 to 300 times.

[0082] Preferably, the ultrasonic spraying is performed 100 to 200 times.

[0083] According to the present invention, the thickness of the magnesium fluoride antireflection film in step S8 is 10-200 nm.

[0084] Preferably, the magnesium fluoride antireflection film has a thickness of 50-150 nm.

[0085] According to the present invention, the thickness of the solar cell in step S8 is 10-200 nm.

[0086] Preferably, the magnesium fluoride antireflection film has a thickness of 50-150 nm.

[0087] According to the present invention, the power of the solar cell in step S8 is 10-200w.

[0088] According to the present invention, the temperature of the hot pressing in step S8 is 100-200°C and the pressure is 0.5-10 kg / cm 2 , the time is 100 to 150 seconds.

[0089] Preferably, the temperature of the hot pressing is 120-160°C and the pressure is 1-5 kg / cm 2 , the time is 110 to 130 seconds.

[0090] Comparative Example 1

[0091] 1mmol zirconium chloride, 0.1mmol bismuth chloride, 0.005mmol ytterbium chloride hexahydrate and 10ml hydrochloric acid were fully mixed and stirred. After zirconium chloride, bismuth chloride and ytterbium chloride hexahydrate were fully dissolved, 10ml hydrochloric acid solution containing cesium chloride (cesium chloride concentration was 0.2mmol / L) was dropped. A white precipitate was immediately generated in the solution. The mixture was heated and stirred at 80°C for 30min, cooled and allowed to stand to room temperature, and washed by centrifugation with methanol for 3 times to obtain wet double perovskite. The wet double perovskite was dried at 80°C for 3h and then ground to obtain Bi 3+ , Yb 3+Co-doped Cs2ZrCl6 double perovskite microcrystals have a crystallinity of 65.72% and a photoluminescence quantum yield of 64.34%.

[0092] 1mmol of the above Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals were dissolved in 1 ml of ethanol to prepare a microcrystalline solution, which was then sprayed by an ultrasonic sprayer (300 cm / min, 150 times) to prepare a microcrystalline film. The microcrystalline film, magnesium fluoride antireflection film (50 nm thick) and solar cell (50 nm thick, 20 W power) were hot pressed (temperature 120 °C, pressure 5 kg / cm 2 , time 120s) to obtain a light conversion material. The light conversion material can increase the light conversion efficiency of polycrystalline silicon or amorphous silicon solar panels from 23% to 23.5%.

[0093] Example 1

[0094] 8g of ionic liquid (1-hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt) was preheated at 80°C for 30min, and then 1mmol of zirconium chloride, 0.1mmol of bismuth chloride, and 0.005mmol of ytterbium chloride hexahydrate were fully mixed and stirred with the ionic liquid. After zirconium chloride, bismuth chloride, and ytterbium chloride hexahydrate were fully dissolved, 10ml of hydrochloric acid solution containing cesium chloride (cesium chloride concentration was 0.2mmol / L) was dropped, and a white precipitate was immediately generated in the solution. The solution was heated and stirred at 50°C for 100min, cooled and allowed to stand to room temperature, and washed by centrifugation with methanol three times to obtain wet double perovskite. The wet double perovskite was dried at 60°C for 24h, and then ground to obtain Bi 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals. The crystallinity of the double perovskite microcrystals is 73.98%, and the photoluminescence quantum yield is 74.86%. 3+ It can then achieve efficient blue light emission at 455nm and enhance the luminescence performance in the near-infrared region. Figure 1 It is the fluorescence excitation spectrum and fluorescence emission spectrum.

[0095] 1mmol of the above Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals were dissolved in 1 ml of ethanol to prepare a microcrystalline solution, which was then sprayed by an ultrasonic sprayer (300 cm / min, 150 times) to prepare a microcrystalline film. The microcrystalline film, magnesium fluoride antireflection film (50 nm thick) and solar cell (50 nm thick, 20 W power) were hot pressed (temperature 120 °C, pressure 5 kg / cm 2, time 120s) to obtain a light conversion material. The light conversion material can increase the light conversion efficiency of polycrystalline silicon or amorphous silicon solar panels from 23% to 23.6%.

[0096] Example 2

[0097] 8g of ionic liquid (1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt) was preheated at 90°C for 20min, and then 1mmol of zirconium sulfate, 0.1mmol of bismuth nitrate, and 0.05mmol of ytterbium chloride hexahydrate were fully mixed and stirred with the ionic liquid. After zirconium sulfate, bismuth nitrate, and ytterbium chloride hexahydrate were fully dissolved, 10ml of phosphoric acid solution containing cesium carbonate (cesium carbonate concentration was 0.3mmol / L) was dropped. A white precipitate was immediately generated in the solution. The solution was heated and stirred at 100°C for 20min, cooled and allowed to stand to room temperature, and washed by centrifugation with ethanol 4 times to obtain wet double perovskite. The wet double perovskite was dried at 100°C for 1h, and then ground to obtain Bi 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals. The crystallinity of the double perovskite microcrystals is 80.72%, and the photoluminescence quantum yield is 78.52%. 3+ It can then achieve efficient blue light emission at 455nm and enhance the luminescence performance in the near-infrared region. Figure 2 It is the fluorescence excitation spectrum and fluorescence emission spectrum.

[0098] 2mmol of the above Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals were dissolved in 1 ml of methanol to prepare a microcrystalline solution, which was then sprayed by an ultrasonic sprayer (speed 600 cm / min, times 200 times) to prepare a microcrystalline film. The microcrystalline film, magnesium fluoride antireflection film (thickness 150 nm) and solar cell (thickness 100 nm, power 200 W) were hot pressed (temperature 160 ° C, pressure 1 kg / cm 2 , time 120s) to obtain a light conversion material. The light conversion material can increase the light conversion efficiency of polycrystalline silicon or amorphous silicon solar panels from 23% to 24%, and achieve efficient blue light emission.

[0099] Example 3

[0100] 8g of ionic liquid (1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide salt) was preheated at 70°C for 40min, and then 1mmol of zirconium nitrate, 0.1mmol of bismuth sulfate, and 0.1mmol of ytterbium sulfate octahydrate were fully mixed and stirred with the ionic liquid. After zirconium nitrate, bismuth sulfate, and ytterbium chloride hexahydrate were fully dissolved, 10ml of sulfuric acid solution containing cesium sulfate (cesium sulfate concentration was 0.1mmol / L) was dropped. A white precipitate was immediately generated in the solution. The solution was heated and stirred at 70°C for 40min, cooled and allowed to stand to room temperature, and washed by centrifugation with ethyl acetate for 6 times to obtain wet double perovskite. The wet double perovskite was dried at 80°C for 10h, and then ground to obtain Bi 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals. The crystallinity of the double perovskite microcrystals is 63.21%, and the photoluminescence quantum yield is 65.58%. 3+ It can then achieve efficient blue light emission at 455nm and enhance the luminescence performance in the near-infrared region. Figure 3 It is the fluorescence excitation spectrum and fluorescence emission spectrum.

[0101] 5mmol of the above Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals were dissolved in 1 ml of toluene to prepare a microcrystalline solution, which was then sprayed by an ultrasonic sprayer (speed 200 cm / min, 100 times) to prepare a microcrystalline film. The microcrystalline film, magnesium fluoride antireflection film (thickness 100 nm) and solar cell (thickness 150 nm, power 100 W) were hot pressed (temperature 150 ° C, pressure 3 kg / cm 2 , time 120s) to obtain a light conversion material. The light conversion material can increase the light conversion efficiency of polycrystalline silicon or amorphous silicon solar panels from 23% to 23.7%.

Claims

1. Bi 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals, characterized in that The invention uses an ionic liquid as a solvent, dissolves a cesium salt, a zirconium salt, a bismuth salt and a ytterbium salt in the ionic liquid, and obtains the product through a coprecipitation method.

2. Preparation of Bi as claimed in claim 1 3+ , Yb 3+ A method for co-doping Cs2ZrCl6 double perovskite microcrystals, characterized in that: The method comprises the following steps: S1 heats and melts the ionic liquid; the ionic liquid is one of imidazole hexafluorophosphate, imidazole tetrafluoroborate, imidazole chloride, imidazole bromide, imidazole acetate, imidazole trifluoroacetate and imidazole nitrate; the heating temperature is 60-100° C., and the heating time is 10-100 min; S2: mixing, stirring and dissolving zirconium salt, bismuth salt and ytterbium salt with the ionic liquid to obtain a mixed solution; the molar ratio of the zirconium salt, bismuth salt and ytterbium salt is 10:1:0.005-2; the concentration of the zirconium salt, bismuth salt and ytterbium salt in the ionic liquid is 0.01-1 mmol / mL; S3: dripping the acid solution of cesium salt into the mixed solution, immediately generating white precipitate, continuing heating and stirring, then cooling and standing to room temperature, pouring out the upper clear liquid, and the lower solution is a double perovskite microcrystalline solution; the concentration of the cesium salt is 0.05-0.5 mmol / mL; the molar ratio of the cesium salt to the zirconium salt in step S2 is 2:0.1-5; the heating temperature is 50-100°C; the stirring time is 20-100 min; S4 centrifugally wash the double perovskite microcrystal solution with an organic solvent to obtain wet double perovskite microcrystals; S5 is obtained by drying and grinding the wet double perovskite microcrystals.

3. The method according to claim 2, characterized in that In step S2, the zirconium salt is a mixture of one or more of zirconium chloride, zirconium nitrate, zirconium sulfate, zirconium carbonate and zirconium acetate; the bismuth salt is a mixture of one or more of bismuth trichloride, bismuth sulfate, bismuth carbonate and bismuth hydroxide; the ytterbium salt is a mixture of one or more of ytterbium trichloride, ytterbium nitrate, ytterbium carbonate, ytterbium sulfate and ytterbium hydroxide.

4. The method according to claim 2, characterized in that: The dissolving temperature in step S2 is 50-100°C.

5. The method according to claim 2, characterized in that: In step S3, the cesium salt is a mixture of one or more of cesium chloride, cesium sulfate, cesium nitrate, cesium carbonate and cesium hydroxide; and the acid is one of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid.

6. The method according to claim 2, characterized in that In step S4, the organic solvent is one of ethanol, methanol, ethyl acetate, carbon dichloride, trichloroethylene, carbon tetrachloride, cyclohexane and n-hexane; and the mixture is centrifuged and washed 2 to 6 times.

7. The method according to claim 2, characterized in that The drying temperature in step S5 is 60-100° C., and the drying time is 1-24 hours.

8. A method for preparing a light-converting film, characterized in that: The following steps are involved: First, the Bi is prepared by any method described in claim 2 to 7. 3+ , Yb 3+ Co-doped Cs2ZrCl6 double perovskite microcrystals; S6 will Bi 3+ , Yb 3+ The co-doped Cs2ZrCl6 double perovskite microcrystals are dissolved in a solvent to prepare a microcrystal solution; S7 forming the microcrystalline solution into a microcrystalline film through an ultrasonic spraying machine; S8: hot pressing the microcrystalline thin film, magnesium fluoride antireflection film and solar cell in sequence.

9. The preparation method according to claim 8, characterized in that: The solvent in step S6 is a mixture of one or more of methanol, ethanol and toluene; 3+ , Yb 3+ The concentration of co-doped Cs2ZrCl6 double perovskite microcrystals is 0.5-10mmol / ml; the speed of ultrasonic spraying in step S7 is 100-1000cm / min; the number of ultrasonic spraying in step S7 is 50-300 times; the thickness of the magnesium fluoride antireflection film in step S8 is 10-200nm; the thickness of the solar cell in step S8 is 10-200nm; the power of the solar cell in step S8 is 10-200w; the temperature of hot pressing in step S8 is 100-200℃, and the pressure is 0.5-10kg / cm 2 , the time is 100 to 150 seconds.

Citation Information

Patent Citations

  • Perovskite quantum dot-polymer composite film and preparation method thereof

    CN114702949A